Does a single specialty intensive care unit make better business sense than a multi-specialty intensive care unit? A costing study in a trauma center in India - Parmeshwar Kumar; Vishwanathan Jithesh; Shakti Kumar Gupta (Saudi Journal of Anaesthesia, 2015)
Context: Though intensive care units (ICUs) only account for 10% of hospital beds, they consume nearly 22% of hospital resources. Few definitive costing studies have been conducted in Indian settings that would help determine appropriate resource allocation. Aim: To evaluate and compare the cost of intensive care delivery between multi-specialty and neurosurgery ICU in an apex trauma care facility in India. Materials and Methods: The study was conducted in a polytrauma and neurosurgery ICU at a 203 bedded level IV trauma care facility in New Delhi, India from May, 2012 to June 2012. The study was cross-sectional, retrospective, and record-based. Traditional costing was used to arrive at the cost for both direct and indirect cost estimates. The cost centers included in study were building cost, equipment cost, human resources, materials and supplies, clinical and nonclinical support services, engineering maintenance cost, and biomedical waste management. Statistical Analysis: Fisher′s two-tailed t-test. Results: Total cost/bed/day for the multi-specialty ICU was Rs. 14,976.9/- and for the neurosurgery ICU was Rs. 14,306.7/-, manpower constituting nearly half of the expenditure in both ICUs. The cost center wise and overall difference in the cost among the ICUs were statistically significant. Conclusions: Quantification of expenditure in running an ICU in a trauma center would assist healthcare decision makers in better allocation of resources. Although multi-specialty ICUs are more expensive, other factors will also play a role in defining the kind of ICU that need to be designed.